The first films of Akira Kurosawa [videorecording (DVD)]. - Kurosawa, Akira, 1910-1998; Ōkōchi, Denjirō, 1898-1962; Fujita, Susumu, 1912-1991; Namiki, Gohei, 1789-1855 (Eclipse (Criterion Collection (Firm)). First films of Akira Kurosawa., 2010)
While young Sanshiro is enrolled in a jujitsu school, he also secretly studies the more spiritual art of judo; follows the stories of several female volunteer workers at an optics plant during World War II; Sanshiro becomes the target of revenge; Lord Yoshitsune and his samurai bodyguards dress as monks in order to pass through enemy territory.